Museum Digital Ulos Berbasis Android - Januardi Rosyidi Lubis; Deka Maita Sandi (Jurnal Basicedu, 2021)
Museum is an educational institution where tangible (fossils, artifacts) and intangible (values, traditions, norms) are displayed. The museum in Medan has various range of but there has been no inventory of the Ulos as a Bataknese traditional ethnic cloth yet as one of the cultural identities of native people in North Sumatera, Indonesia. By using Android platform, this study aims to analyze and explain various patterns and motifs of the Batak Ulos in 6 (six) regencies: Karo, Pak-pak, Simalungun, Toba Samosir, Tapanuli, and Mandailing. The problems were (1) designing a digital Ulos museum using Android software, (2) describing and explaining the various motifs of Ulos representating each region, and (3) explaining noble values contained in Ulos. Therefore, people nowadays can safe time and distance as well as easily find information about the use, the meaning, and the function of each Ulos. This study uses the ADDIE (Analysis Design - Development - Implement - Evaluate) method. The results of this study are in the form of an android-based application that can be distributed offline to students, teachers, and the general public. In the future, this research is expected to develop applications that can be accessed online through various Playstores.